Analysis of the relationship between LET, γH2AX foci volume and cell killing effect of carbon ions using high-resolution imaging technology. (7th January 2023) - Oike, Takahiro; Kakoti, Sangeeta; Sakai, Makoto; Matsumura, Akihiko; Ohno, Tatsuya; Shibata, Atsushi
Abstract: The strong cell killing effect of high linear energy transfer (LET) carbon ions is dependent on lethal DNA damage. Our recent studies suggest that induction of clusters of double-strand breaks (DSBs) in close proximity is one of the potential mechanisms. However, the relationship between LET, the degree of DSB clustering and the cell killing effect of carbon ions remains unclear. Here, we used high-resolution imaging technology to analyze the volume of γH2AX foci induced by monoenergetic carbon ions with a clinically-relevant range of LET (13–100 keV/μm). We obtained data from 3317 γH2AX foci and used a gaussian function to approximate the probability ( p ) that 1 Gy-carbon ions induce γH2AX foci of a given volume ( vth ) or greater per nucleus. Cell killing effects were assessed in clonogenic assays. The cell killing effect showed high concordance with p at vth  = 0.7 μm 3 across various LET values; the difference between the two was 4.7% ± 2.2%. This relationship was also true for clinical carbon ion beams harboring a mixed LET profile throughout a spread-out Bragg peak width (30–120 mm), with the difference at vth  = 0.7 μm 3 being 1.6% ± 1.2% when a Monte Carlo simulation-derived dose-averaged LET was used to calculate p . These data indicate that the cell killing effect of carbon ions is predictable by the ability of carbon ions to induce γH2AX foci containing clustered DSBs, which is linked to LET, providing the biological basis for LET modulation in the planning of carbon ion radiotherapy.